Violation and the inscription of opposites in The Homeric Hymn to Demeter and Bram Stoker’s Dracula (Journal for Studies in Humanities and Social Sciences, 2015)
Part of the power of myths and symbols is held to lie in their capacity to encompass opposites. This paper proposes that the mythologem of a male violation of a virginal female victim is inscripted to represent the opposites of fertility and infertility in the Homeric Hymn to Demeter and Bram Stoker’s Dracula, which represent the rape of Persephone by Hades and the vampiric attack on Lucy Westenra by Dracula, respectively. The opposition emerges partly in the fate of the victim. In the Homeric Hymn, Persephone is taken from above ground to the underworld by Hades, an allegory of the planting of the corn seed, which further symbolizes the cycle of fertility in which life emerges from death, as indicated by Kerényi (2002a). In Dracula, Lucy Westenra does not make this journey. When she dies after Dracula’s attack, she is not truly dead, neither above nor below, but trapped in the middle, as one of the Undead. This version of the mythologem may thus be said to represent infertility. This conclusion may be sharpened in the light of a common reading of Dracula as refl ecting the anxieties of Bram Stoker’s Victorian society about women’s sexuality. Lucy’s transformation into a vampire is accompanied by an increased sexual boldness towards the men around her. This voluptuousness suggests unchastity, the “fate worse than death”, represented by the fate of being undead. Unchastity in this light is opposed to, not fertility perse, but to socially sanctioned fertility.